2015
DOI: 10.1371/journal.pgen.1005607
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Craniofacial Traits in Outbred Mice Identifies Major Developmental Genes Involved in Shape Determination

Abstract: The vertebrate cranium is a prime example of the high evolvability of complex traits. While evidence of genes and developmental pathways underlying craniofacial shape determination is accumulating, we are still far from understanding how such variation at the genetic level is translated into craniofacial shape variation. Here we used 3D geometric morphometrics to map genes involved in shape determination in a population of outbred mice (Carworth Farms White, or CFW). We defined shape traits via principal compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(145 citation statements)
references
References 117 publications
11
128
2
4
Order By: Relevance
“…In this study, using a phenotype-focused approach, we find patterns that support a highly polygenic basis for between-subspecies differences. Different experimental approaches (GWAS, congenic lines, consomic panels) using different type of mice (inbred, outbred, wild) have found a positive correlation between the length of genomic fragments and the magnitude of their effect on craniofacial shape (Burgio et al 2009(Burgio et al , 2012Pallares et al 2014Pallares et al , 2015. Here we also find a strong positive correlation between genomic distance and phenotypic distance.…”
Section: 49supporting
confidence: 69%
See 2 more Smart Citations
“…In this study, using a phenotype-focused approach, we find patterns that support a highly polygenic basis for between-subspecies differences. Different experimental approaches (GWAS, congenic lines, consomic panels) using different type of mice (inbred, outbred, wild) have found a positive correlation between the length of genomic fragments and the magnitude of their effect on craniofacial shape (Burgio et al 2009(Burgio et al , 2012Pallares et al 2014Pallares et al , 2015. Here we also find a strong positive correlation between genomic distance and phenotypic distance.…”
Section: 49supporting
confidence: 69%
“…Using a GWAS approach, we have previously shown that the genetic architecture of within-population craniofacial shape variation in the mouse is highly polygenic (Pallares et al 2015). In this study, using a phenotype-focused approach, we find patterns that support a highly polygenic basis for between-subspecies differences.…”
Section: 49supporting
confidence: 54%
See 1 more Smart Citation
“…In humans, loss of ALX1 is causing frontonasal dysplasia (OMIM #136760) [18]. In a recently published study, Pallares and colleagues were able to map within population variance of craniofacial shape of inbred mice [19]. Furthermore, they identified 17 loci responsible for variation in skull shape and eight loci responsible for variation in mandible shape of these mice, with Mn1 as a key gene in skull formation and within population shape variation.…”
Section: Animal Studiesmentioning
confidence: 99%
“…During this early phase, shape was still mainly described by multiple linear measurements and distances and the major problem of capturing the geometry or overall shape of a complex structure persisted. In the 1980s, advances in the development of statistical analytic tools and their combination with outline and landmark data revolutionized the field of geometric morphometrics (Zelditch et al 2012;Rohlf and Marcus 1993;Adams et al 2004;Mitteroecker and Gunz 2009;Adams et al 2013) and sparked studies in facial expression (Adams et al 2013), shape-to-body size correlation (allometry) (Sidlauskas et al 2011), symmetry (Klingenberg et al 2002), quantitative genetics (Klingenberg and Leamy 2001;Boell et al 2011;Pallares et al 2015) and evolutionary-developmental biology (Klingenberg 2010;Salazar-Ciudad and Jernvall 2010) to name but a few.…”
Section: Shape: Description and Quantification Of Complex Structuresmentioning
confidence: 99%